2015
DOI: 10.5539/jas.v7n11p59
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Two Simulated Green Roofs in the Mediterranean Area

Abstract: The green roofs sector is a relatively recent phenomenon in Mediterranean countries, meaning that as yet there is no complete understanding of which plants are suited to this particular environment. Such plants would need to be adaptable to the green roof itself as well as to the drought and intense lighting typical of a Mediterranean summer. Two simulated green roofs were planted with a variety of species and life forms and subjected to two minimal irrigation treatments and one treatment without irrigation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…T. serpyllum, for example, because of its creeping chamaephyte suffruticose habitus, can reduce transpiration (Schulz et al, 2005;Caneva et al, 2015) and more easily tolerate drought. Its use has thus been experimented on green roofs in many Mediterranean areas (Provenzano et al, 2010;Vestrella et al, 2015). At the same time, as indicated by our data during the first period of monitoring, T. serpyllum can develop more quickly than F. ovina, if irrigated, and can sometimes become dominant (Vestrella et al, 2015).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…T. serpyllum, for example, because of its creeping chamaephyte suffruticose habitus, can reduce transpiration (Schulz et al, 2005;Caneva et al, 2015) and more easily tolerate drought. Its use has thus been experimented on green roofs in many Mediterranean areas (Provenzano et al, 2010;Vestrella et al, 2015). At the same time, as indicated by our data during the first period of monitoring, T. serpyllum can develop more quickly than F. ovina, if irrigated, and can sometimes become dominant (Vestrella et al, 2015).…”
Section: Discussionsupporting
confidence: 63%
“…Its use has thus been experimented on green roofs in many Mediterranean areas (Provenzano et al, 2010;Vestrella et al, 2015). At the same time, as indicated by our data during the first period of monitoring, T. serpyllum can develop more quickly than F. ovina, if irrigated, and can sometimes become dominant (Vestrella et al, 2015).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…For this reason, only relatively recently modern green roofs started being installed in Mediterranean cities. In the same period, scientific interest in designing and establishing Mediterranean green roofs has increased (Benvenuti and Bacci, 2010;Provenzano, 2011;Caneva et al, 2013;Kotsiris et al, 2013;Papafotiou et al, 2013;Raimondo et al, 2015;Vestrella et al, 2015b). Relevant scientific literature has investigated which plants are more suited for Mediterranean green roofs and studies have generally shown that certain plant taxa and xerophytes or succulent plants are the most appropriate for them (e.g., Provenzano, 2011;Papafotiou et al, 2013;Tassoula et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these multiple requirements, the selection of plant material suitable for extensive green roofs has pointed toward the exploration of native and endemic species adapted to specific areas and climatic zones [1,2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Despite these efforts, there is still a lack of documentation, and a lot of further research is necessary to take advantage of the huge resources offered by native Mediterranean plants in the agricultural, horticultural and landscape industries [23].…”
Section: Introductionmentioning
confidence: 99%